Hepatocyte growth factor inhibits hypoxia/reoxygenation-induced activation of xanthine oxidase in endothelial cells through the JAK2 signaling pathway - Zhang, Ying Qian (Int J Mol Med, 2016)
Vascular endothelial cells (ECs) appear to be one of the primary targets of hypoxia/reoxygenation (H/R) injury. In our previous study, we demonstrated that hepatocyte growth factor (HGF) exhibited a protective effect in cardiac microvascular endothelial cells (CMECs) subjected to H/R by inhibiting xanthine oxidase (XO) by reducing the cytosolic Ca(2+) concentration increased in response to H/R. The precise mechanisms through which HGF inhibits XO activation remain to be determined. In the present study, we examined the signaling pathway through which HGF regulates Ca(2+) concentrations and the activation of XO during H/R in primary cultured rat CMECs. CMECs were exposed to 4 h of hypoxia and 1 h of reoxygenation. The protein expression of XO and the activation of the phosphoinositide 3-kinase (PI3K), janus kinase 2 (JAK2) and p38 mitogen-activated protein kinase (p38 MAPK) signaling pathways were detected by western blot analysis. Cytosolic calcium (Ca(2+)) concentrations and reactive oxygen species (ROS) levels were measured by flow cytometry. The small interfering RNA (siRNA)-mediated knockdown of XO inhibited the increase in ROS production induced by H/R. LY294002 and AG490 inhibited the H/R-induced increase in the production and activation of XO. The PI3K and JAK2 signaling pathways were activated by H/R. The siRNA-mediated knockdown of PI3K and JAK2 also inhibited the increase in the production of XO protein. HGF inhibited JAK2 activation whereas it had no effect on PI3K activation. The siRNA-mediated knockdown of JAK2 prevented the increase in cytosolic Ca(2+) induced by H/R. Taken together, these findings suggest that H/R induces the production and activation of XO through the JAK2 and PI3K signaling pathways. Furthermore, HGF prevents XO activation following H/R primarily by inhibiting the JAK2 signaling pathway and in turn, inhibiting the increase in cytosolic Ca(2+).